2017
DOI: 10.2196/jmir.6895
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Depressive Symptoms and Psychosocial Stressors on Twitter: A Corpus-Based Study

Abstract: BackgroundWith a lifetime prevalence of 16.2%, major depressive disorder is the fifth biggest contributor to the disease burden in the United States.ObjectiveThe aim of this study, building on previous work qualitatively analyzing depression-related Twitter data, was to describe the development of a comprehensive annotation scheme (ie, coding scheme) for manually annotating Twitter data with Diagnostic and Statistical Manual of Mental Disorders, Edition 5 (DSM 5) major depressive symptoms (eg, depressed mood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 39 publications
2
84
0
2
Order By: Relevance
“…This suggests that the time-structured patterns of emotion expressed on Facebook may provide better differentiation between individuals with and without depression where they express similar levels of negative emotion words. The current study suggests that the poor hit rate in some keyword approaches to classifying depression in status updates, as described by Mowery et al [15], may be enhanced by including measures of moment-to-moment variability in emotion word use.…”
Section: Negative Affect Instability On Facebookmentioning
confidence: 68%
See 4 more Smart Citations
“…This suggests that the time-structured patterns of emotion expressed on Facebook may provide better differentiation between individuals with and without depression where they express similar levels of negative emotion words. The current study suggests that the poor hit rate in some keyword approaches to classifying depression in status updates, as described by Mowery et al [15], may be enhanced by including measures of moment-to-moment variability in emotion word use.…”
Section: Negative Affect Instability On Facebookmentioning
confidence: 68%
“…For instance, Moreno et al [3] demonstrated that status updates on Facebook displaying references to depression symptoms, such as hopelessness, positively correlated with self-reported depression symptoms. Others have extended this by describing the linguistic characteristics of depression in posts and developing coding-schemes to identify depression-indicative Tweets or status updates [2,4,7,15]. While specific topics, keywords, and linguistic features (notably negative emotions) are able to identify depression-indicative posts with high sensitivity, many of these features may also be present in posts that are nonindicative of depression (low specificity).…”
Section: Depression In Status Updates On Social Mediamentioning
confidence: 99%
See 3 more Smart Citations